Low dose peripheral systemic thrombolysis for treatment of intermediate–high risk acute pulmonary embolism: a case series. Issue 10 (12th October 2022) - Charif, Fida; Khatoun, Houda; Nassar, Pierre; Jouni, Aya; Jaber, Sadek; Moussa, Malek; Choumar, Bilal; Karrowni, Wassef
Abstract: Background: The management of intermediate–high-risk acute pulmonary embolism (PE) is controversial with increasing interest in more aggressive treatment approaches than anticoagulation alone. Case summary: We describe the case series of four consecutive patients who presented to emergency room for acute shortness of breath. They were diagnosed with intermediate–high-risk acute PE based on the computed tomography pulmonary angiography and transthoracic echocardiography (TTE) findings and the elevated simplified PE score index. They received bolus of 5 mg thrombolytics recombinant tissue plasminogen activator (rtPA) administered through peripheral intravenous (i.v.) line followed by continuous infusion at a rate of 2 mg/h along with unfractionated heparin (UFH) at a rate of 500 mg/h for additional ≤10 h. There after the dose of UFH was increased to reach a therapeutic level. Rapid clinical improvement and also improvement in TTE parameters were noted at discharge. Patients were discharged home on oral anticoagulation. Discussion: Intermediate–high-risk acute PE carries increased risk of mortality and morbidities. Catheter-directed thrombolysis uses a low rtPA dose for local thrombolysis and is associated with low bleeding risk; however it is expensive and requires expertise and human resources. Low-dose rtPA through a peripheral i.v. line might be safe and effective in the treatment of patient with intermediate–high-risk acute PE. This therapeutic approach is readily available at most medical centres, can be started in the emergency room (ER), and can be alternative to catheter-directed thrombolysis nowadays during the COVID-19 era and in hospitals at the periphery and with limited resources.